Arabeeziyah in the social media sites and its effect on the Arabic of the upper basic stage students in Marka District government Schools - Al-Shraydeh, Mohammad; Jundyeh, Hana (Dirasat: Human and Social Sciences, 2020)
Based on the assumption that the young generation at the upper level of school realize the importance of Arabic and the necessity of preserving it, the study polled those youth through a questionnaire about the communication phenomenon known as "Arabeeziyah" , the new hybred by which the Arabic tongue yielded to the latin letters , and , thus , the transcription has become mixed up, and some Arabic letters are replaced by latin numbers leading to commonly- used colloquial dialects within the same country , the study included that this phenomenon is incidental and strange , but it brings along dangerous dimensions that affect the user’s Arabic , and even his cultural identity ,and detaches him from his great heritage. The results at the study are promising because those polled realized the danger at this kind of communication which they ascribed to a typical behavior that would soon end. Never the less ,the study called for paying attention to the responsibity of curing the phenomenon by teaching good standard Arabic ,and enriching the computer with relevant Arabic programs